1999
DOI: 10.1002/(sici)1521-4141(199901)29:01<334::aid-immu334>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone prevents human monocytic cells from Fas-mediated apoptosis by up-regulating Bcl-2 expression

Abstract: Apoptosis and particularly Fas-mediated apoptosis has been proposed to play a key role in controlling monocyte homeostasis. We and others have documented the regulatory function of human growth hormone (hGH) on monocytic cells, which prompted us to investigate the role of hGH on their response to Fas antigen cross-linking. Using human promonocytic U937 cells constitutively producing hGH upon gene transfer and human primary monocytes cultured in the presence of recombinant hGH, we demonstrated that hGH diminish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 57 publications
3
4
0
Order By: Relevance
“…Additionally, the marked protection of U937 cells from Fas-mediated apoptosis by Flip, but not Bcl-2, supports the importance of Flip for macrophage survival. Recently, stably expressed Bcl-2 was shown to provide modest protection against Fas-mediated apoptosis in U937 cells (53), which was comparable to that observed in our study. Decreased numbers of GFP-positive U937 cells were not seen even when higher concentrations of the Flip expression plasmids were used.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the marked protection of U937 cells from Fas-mediated apoptosis by Flip, but not Bcl-2, supports the importance of Flip for macrophage survival. Recently, stably expressed Bcl-2 was shown to provide modest protection against Fas-mediated apoptosis in U937 cells (53), which was comparable to that observed in our study. Decreased numbers of GFP-positive U937 cells were not seen even when higher concentrations of the Flip expression plasmids were used.…”
Section: Discussionsupporting
confidence: 91%
“…Because GC induces apoptosis in lymphocytes and Bcl-2 is a key molecule for preventing apoptosis, we focused on Bcl-2 expression. It was previously reported that GH increased Bcl-2 expression in human monocytic cells (33). The present observations that rhGH enhances Bcl-2 expression selectively in CD4 + T lymphocytes clearly explain why rhGH raised the CD4 + /CD8 + ratio of T lymphocytes in GC-treated rats.…”
Section: Discussionsupporting
confidence: 76%
“…G, Pascoe DD, unpublished observations). We find this particularly interesting as human growth hormone has been shown to diminish various forms of lymphocyte cell death in vitro by upregulating an essential antiapoptotic protein, Bcl-2 (16,22). Therefore, it is possible that the increased growth hormone in conjunction with the increase in antioxidant enzyme activity following HIIT may be responsible for maintaining lymphocyte function.…”
Section: Discussionmentioning
confidence: 97%